Gender Differences in Worry About a Terrorist Attack: a Cross-National Examination of Individual- and National-Level Factors - Dillon, Leevia (Women & criminal justice, 2019)
Prior research has found gender to be associated with worry about crime and terrorism. We used World Values Survey data to assess gender differences in worry about terrorism across 54 nations. Analyses also examined the influence of individual- and national-level factors. Women were significantly more worried about terrorism in 22 of the 54 nations. Men in Iraq, Libya, Yemen, and New Zealand were significantly more worried about terrorism than women. Individuals were more likely to worry about terrorism as the nation’s average mortality count in terrorist incidents increased. Policy implications and directions for future research are discussed.